Clinical significance of the largest histopathological metastatic lymph node size for postoperative course of patients undergoing surgery for gastric cancer - Omeroglu, Sinan; Gulmez, Selcuk; Yazici, Pinar; Demir, Uygar; Guven, Onur; Capkinoglu, Emir; Uzun, Orhan; Senger, Aziz Serkan; Polat, Erdal; Duman, Mustafa (Frontiers in Surgery, 2023)
Aim: The aim of this study was to investigate the effect of the largest metastatic lymph node (MLN) size on postoperative outcomes of patients with stage II-III gastric cancer (GC). Methods: A total of 163 patients with stage II/III GC who underwent curative surgery were included in this single-center retrospective study. The lymph nodes were counted, each lymph node was analyzed for metastatic involvement by histopathological examination, and the diameter of the largest metastatic lymph node was recorded. The severity of postoperative complications was assessed by Clavien–Dindo classification system. Two groups of 163 patients were defined according to ROC analysis with cut-off value of histopathologically maximum MLN diameter. A comparative analysis of demographic and clinicopathological characteristics of the patients and their postoperative outcomes were performed. Results: The median hospital stay was significantly longer in patients with major complications compared to patients without major complications [18 days (IQR: 13-24) vs. 8 days (IQR: 7-11) ; (p<0.001)]. The median MLN size was significantly larger in deceased patients compared to survived [1.3 cm (IQR: 0.8-1.6) vs. 0.9 cm (IQR: 0.6-1.2), respectively ; (p<0.001)]. The cut-off value of MLN size predicting mortality was found as 1.05 cm. MLN size ≥1.05 cm had nearly 3.5 times more negative impact on survival. Conclusions: The largest metastatic lymph node size had a significant association with survival outcomes. Particularly, MLN size over 1.05 cm was associated with worse survival outcomes. However, the largest MLN was not shown to have any effect on major complications. Further prospective and large-scale studies are required to draw more precise conclusions.